Analysis Of The Independence Ratio, Harmony Ratio, Efficiency Ratio And Effectiveness Ratio In Assessing The Performance Of The Village Revenue And Expenditure Budget (APBDES) Of Hiliweto Idanoi, Kec, Gunungsitoli Idanoi, Gunungsitoli City (2021-2023 Peri - Torisman Halawa; Dedi Irawan Zebua (UNIVED Press, 2025)
This study aims to assess the financial performance of Hiliweto Idanoi Village, Gunungsitoli Idanoi District, Gunungsitoli City, through an analysis of the independence, harmony, efficiency, and effectiveness ratios in the Village Revenue and Expenditure Budget (APBDes) during the 2021-2023 period. This analysis is important to determine the extent to which the village is able to manage its income and expenditure in order to achieve sustainable development. The Independence Ratio is still low, indicating a high dependence on transfer funds from the central and regional governments, with minimal contributions to Village Original Income (PADes). The Harmony Ratio reveals regularity in spending allocation, where operational spending is more dominant than capital spending, which can affect village development in the future. The Efficiency Ratio shows that overall village spending management is quite efficient, although there are some increases in spending that are not yet fully optimal. The Effectiveness Ratio throughout the study period, with several years successfully achieving revenue targets. Based on these results, it is recommended that the village government increase efforts to explore the potential of Village Original Income (PADes), improve the balance of operational and capital spending, and strengthen planning so that budget management is more effective and sustainable.